Top-down natural language query approach for embodied conversational agent - Goh, Ong Sing; Depickere, Arnold; Fung, Chun Che; Wong, Kok Wai (International Association of Engineers (IAENG), 2006)
This paper describes research work in implementing a conversational intelligent agent on the web focusing on a top-down natural language query approach. While the present World-Wide Web provides a distributed hypermedia interface to the vast amount of information on the Internet, there is a lack of appropriate metadata to that content. Instead of being a giant library as intended, increasing sections of the Web are looking like a giant dump. A multi-level natural language query system is described in this paper for the representation of knowledge in specific and open domains. The six layers system includes spell check, Natural Language Understanding and Reasoning, FAQChat, Metadata Index Search, Pattern matching and case-based reasoning, and, semi-automated matching approach. Extracts from queries on the field of pandemic crisis, Bird Flu H5N1 is demonstrated.